(untitled) (Research, Society and Development, 2021)
Medical and dental health plans present a significant expansion in Brazil, so it becomes necessary to analyze the characteristics of this type of service provision, as part of a health care model. The objective of this study was to carry out a descriptive analysis of the medical and dental health plan operators in Brazil and the characteristics of their beneficiaries in the period from 2009 to 2019.This is a research conducted through a descriptive analysis of data provided by ANS online registration platform. The following variables were analyzed from 2009 to 2019: number of operators and modalities, age group, type of plan and gender of beneficiaries. In 2009 there were 1498 health insurance operators and in 2019, there were 1022. As for beneficiaries, there were 55 million beneficiaries in 2009 and in 2019 72 million were verified, with a predominance of 53% females aged 34 to 38 years and collective corporate mode, for both medical and dental care coverage. It was concluded that there was a significant growth in the number of beneficiaries of health plans, however there was a decrease in the number of operators from 2009 to 2019.